Exposure to anti-prostitution campaign and the level of awareness and knowledge of Rizal Estanzuela Residents and sex workers in Iloilo City towards task force on moral and values formation's anti-prostitution campaign - Bayonita, Erlyn Isabela
This study aims to determine the exposure to anti-prostitution campaign and the level of awareness and knowledge of the residents of Rizal Estanzuela and the sex workers in Iloilo City towards Task Force on Moral and Values Formation?s anti-prostitution campaign. It also intends to assess the needs of the existing campaign. It follows two sampling procedures: simple random sampling and purposive sampling procedure. The results will then be the basis for the production of the campaign materials. The respondents of this study will consist of both sex workers and residents of Rizal Estanzuela, Iloilo City. Based on the results of the study, the researchers found out that the residents of Rizal Estanzuela have average level of awareness and average level of knowledge towards the campaign. Sex workers in Iloilo City have high level of awareness but have average level of knowledge regarding the said campaign.